Values as motivating factors for representatives of generation Z in the Czech Republic and Slovakia within the European context - Dokoupilová, Lucie; Cogiel, Alina; Fero, Martin (Frontiers in Psychology, 2024)
Generation Z is expected to officially surpass the Baby Boomers in the labor market by 2024 and to represent 30% of the global workforce by 2030. In the work environment, they are referred to oxymoronically as competitively ambivalent. Therefore, it is necessary to investigate the reasons for this behavior and to identify initiatives that would facilitate understanding between Generation Z and other generations. The aim of the present study was to find out whether Generation Z in the Czech Republic and Slovakia, which lives in conditions of deepening polarization of society and differentiated opportunities (e.g., in access to education, consumption of goods and services, work and entertainment), exhibits compatible value orientation or whether significant antagonisms exist in the value system. The study utilized the referential Schwartz’s theory of values, which handles universal values dynamically. This theoretical framework was extended to include the dimension of instrumental values that were contextualized in the labor market environment. The results show that the representatives of Generation Z in the Czech Republic and Slovakia prefer collective values (Benevolence and Universalism) in the first two places. However, they subsequently lean toward two individual values (Hedonism and Self-Direction). The comparison of the results in the European context showed the same values being shared by the representatives of Generation Z with preference nuances. The comparison of Generation Z representatives with members of other generations in the European context showed consistency of sharing collective values (Benevolence and Universalism). Discussion: Intergenerational value congruence, as well as knowledge of the difference in preferred values across generations (the collectivism value of Tradition shared by Baby Boomers and Generation X, and Hedonism as an individualism value shared by Generation Y and Generation Z) can help the successful integration of Generation Z representatives in the labor market. A way toward intergenerational synergy can be the recommended strategies for managing Generation Z in the context of career paths: Flexibility of development; Gamification; Mentoring.